Strategi Pembelajaran Langsung Menggunakan Pendekatan Keterampilan Bertanya (Indo-MathEdu Intellectuals Journal, 2024)
Direct learning, or direct instruction is a very effective approach in teaching explicit concepts and skills, especially for students who need more intensive guidance. The questioning skills approach adds value in hands-on learning by encouraging active interaction between teachers and students. This research was conducted through a qualitative approach through the literature study method. The main sources of data for this article are research articles and books that are relevant to the focus of the research. Articles are searched online in various scientific journals that are indexed on google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that the influence of questioning skills on learning outcomes is very significant. Effective communication through questions can improve students' understanding of the material, increase learning motivation, and develop critical and creative thinking skills. Overall, the integration between hands-on learning strategies and questioning skills creates a comprehensive and effective teaching method, which not only improves academic achievement but also builds students' character and skills that are essential for their future. Thus, the application of direct learning strategies using the questioning skills approach is highly recommended to improve the quality of education and student learning outcomes, making them better prepared to face various challenges in the future